Dekolorisasi Kitin Menggunakan Aseton - Putri Rahmadani; Ahmad Fadli; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Chitin is a biopolymer that can be used in the biomedical field. Chitin can be isolated from shrimp waste using chemical methods through deproteination and demineralization processes. To reduce color in chitin required decolorization stage. The purpose of this study was to study the effect of stirring rate and acetone concentration on the decolorization stage on the characteristics of chitin produced and to make mathematical modeling of carotenoid reduction from inside chitin using acetone in the decolorization stage. The research procedure begins with reducing the size of ebi waste into powder sizes. The powder was then reacted with 3.5% NaOH (deproteination), 1:10 (w / v) ratio for 2 h and stirring speed of 150 rpm. The deproteination product is reacted with HCl 1 N (demineralization), 1:15 (w / v) ratio for 1 h and stirring speed of 150 rpm. The demineralization product was decolourized using 60%, 80%, and 100% acetone, a ratio of 1:10 (w / v) at 70 ° C with a stirring rate of 0.150, and 300 rpm for 720 min. Samples were taken every 60 min increments of 5 mL, the solidified yield of the decolorization filtered and dried. The addition of carotenoids in acetone was analyzed using a UV-Vis spectrophotometer. The results showed that the increase of stirring speed and concentration of acetone, carotenoid content in the solvent also increased. The results of colorimeter test for chitin before decolorization had percentage whiteness of 53.2%, while for chitin at 100% acetone concentration with stirring rate 0 rpm and 300 rpm had a whiteness percentage of 57.9% and 70.3 %.Keywords: acetone, decolorization, carotenoid, chitin, shrimp waste